Strategi Pembelajaran Berbasis Masalah dengan Menggunakan Media Berbasis ICT Sekolah Dasar - Muhammad Arif Arif T (Phinisi Integration Review, 2020)
This study aims to determine the level of mastery of the concept of ecosystem balance and animal preservation as a result of student science learning through the application of problem-based learning strategies using ICT-based media in science learning in class VI SD 157 157 Pasaraya, Bontobahari sub-district, Bulukumba district. This research uses a quantitative approach by conducting two cycles of learning. and each cycle consists of 4 activities which are inseparable, namely action planning, action implementation, action observation / evaluation, and reflection of actions aimed at knowing the contribution of learning through the application of problem-based learning strategies using ICT-based media. The results of this study indicate that mastery of the concept of ecosystem balance and animal preservation is increasing through the application of problem-based learning strategies using ICT-based media in natural science learning in class VI of SD Negeri 157 Pasaraya, Bontobahari sub-district, Bulukumba district.